2019
DOI: 10.1111/mec.14982
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of Burkholderia symbionts in the social amoeba farming symbiosis: Prevalence, species, genetic and phenotypic diversity

Abstract: The establishment of symbioses between eukaryotic hosts and bacterial symbionts in nature is a dynamic process. The formation of such relationships depends on the life history of both partners. Bacterial symbionts of amoebae may have unique evolutionary trajectories to the symbiont lifestyle, because bacteria are typically ingested as prey. To persist after ingestion, bacteria must first survive phagocytosis. In the social amoeba Dictyostelium discoideum, certain strains of Burkholderia bacteria are able to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(134 citation statements)
references
References 70 publications
1
124
0
Order By: Relevance
“…They were collected from a variety of locations over a period of years, mostly by our laboratory group [but see (Francis & Eisenberg, ); Table ]. Some of these clones consistently harbored Burkholderia, and subsequent analysis has shown that about 25% of wild D. discoideum harbor one or more Burkholderia species [though the percentage of infected D. discoideum varies significantly in different locations; (Haselkorn et al, )]. The original, wild‐caught host and symbiont pairings have been preserved in glycerol stock, and we refer to these as “native” infections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They were collected from a variety of locations over a period of years, mostly by our laboratory group [but see (Francis & Eisenberg, ); Table ]. Some of these clones consistently harbored Burkholderia, and subsequent analysis has shown that about 25% of wild D. discoideum harbor one or more Burkholderia species [though the percentage of infected D. discoideum varies significantly in different locations; (Haselkorn et al, )]. The original, wild‐caught host and symbiont pairings have been preserved in glycerol stock, and we refer to these as “native” infections.…”
Section: Methodsmentioning
confidence: 99%
“…The original, wild‐caught host and symbiont pairings have been preserved in glycerol stock, and we refer to these as “native” infections. We have found that all D. discoideum ‐associated Burkholderia tested to date can infect D. discoideum clones other than their original host (Haselkorn et al, ) and we call these “non‐native” infections. In this study, all experiments were done with native host–symbiont pairings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction even turns out to induce a “ménage à trois” in which Burkholderia not only forces the otherwise bactivorous amoebae to carry them in their spores but to also become “tolerant” to food bacteria that are normally, in absence of Burkholderia , rapidly killed and degraded in their phagosomes (Shu et al, ). Extended studies now show that several bacteria genera are able to evade phagocytosis and persist in D. discoideum cells and spores through one or more social cycles, creating a form of semistable and mutualistic proto‐microbiome, which might play an important role in supporting D. discoideum growth in nutrient‐poor conditions (Brock et al, ; Haselkorn et al, ).…”
Section: Introductionmentioning
confidence: 99%